Virtual Colorimetric Sensor Array: Single Ionic Liquid for Solvent Discrimination - Galpothdeniya, Waduge Indika S; Regmi, Bishnu P; McCarter, Kevin S; de Rooy, Sergio L; Siraj, Noureen; Warner, Isiah M (Analytical chemistry (Washington), 2015)
There is a continuing need to develop high-performance sensors for monitoring organic solvents, primarily due to the environmental impact of such compounds. In this regard, colorimetric sensors have been a subject of intense research for such applications. Herein, we report a unique virtual colorimetric sensor array based on a single ionic liquid (IL) for accurate detection and identification of similar organic solvents and mixtures of such solvents. In this study, we employ eight alcohols and seven binary mixtures of ethanol and methanol as analytes to provide a stringent test for assessing the capabilities of this array. The UV–visible spectra of alcoholic solutions of the IL used in this study show two absorption bands. Interestingly, the ratio of absorbance for these two bands is found to be extremely sensitive to alcohol polarity. A virtual sensor array is created by using four different concentrations of IL sensor, which allowed identification of these analytes with 96.4–100% accuracy. Overall, this virtual sensor array is found to be very promising for discrimination of closely related organic solvents.